2008
DOI: 10.1038/npre.2008.2413.2
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular effects on cerebral blood flow

Abstract: Withdrawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is also possible that the vestibular system played a role in the postural effect on cerebrovascular CO 2 reactivity. The vestibular system can affect cerebral flow velocity and cerebrovascular resistance when upright, likely an adaptive mechanism to help dilate the cerebral vessels [27]. However, given that we observed greater vasodilation (i.e., hypercapnic slope) when supine when there is no hydrostatic gradient, it seems unlikely the vestibular system had a significant impact on our findings.…”
Section: Effect Of Body Posture On Cerebrovascular Co 2 Reactivitymentioning
confidence: 56%
See 1 more Smart Citation
“…It is also possible that the vestibular system played a role in the postural effect on cerebrovascular CO 2 reactivity. The vestibular system can affect cerebral flow velocity and cerebrovascular resistance when upright, likely an adaptive mechanism to help dilate the cerebral vessels [27]. However, given that we observed greater vasodilation (i.e., hypercapnic slope) when supine when there is no hydrostatic gradient, it seems unlikely the vestibular system had a significant impact on our findings.…”
Section: Effect Of Body Posture On Cerebrovascular Co 2 Reactivitymentioning
confidence: 56%
“…Seven women had natural menstrual cycles. Three women were tested during the follicular phase (range: days 6-14) and four were tested in the luteal phase (range: days [24][25][26][27][28][29][30][31][32][33][34][35]. All women were confirmed not pregnant immediately prior to laboratory testing.…”
Section: Participantsmentioning
confidence: 99%
“…In humans, caloric vestibular stimulation (Cui et al, ), head pitch (Ray and Carter, ; Ray et al, ), and GVS (Bent et al, ; Grewal et al, ; James and Macefield, ; Voustianiouk et al, ) have all been demonstrated to alter sympathetic nerve activity (SNA) (for review, see Yates and Bronstein, ). Similarly, linear acceleration causes transient changes in blood pressure and blood flow (Cui et al, ; Serrador et al, ) that are attenuated in patients with bilateral vestibular deficits (Yates et al, ). Otolith activation by off‐vertical‐axis rotation produces an increase in muscle SNA in‐phase with the component associated with head‐up tilt and a decrease in this activity corresponding to the head‐down tilt component (Kaufmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway maintains homeostasis through constant negative feedback activity. In contrast, the vestibular system appears to influence blood pressure through a more direct and feed‐forward mechanism that modulates blood pressure during changes in posture with respect to gravity (e.g., when rising from a seated or lying position) in order to maintain adequate blood flow to the brain (Dieterich and Brandt, ; Serrador et al, ). The existence of a functional connection between the vestibular system and blood pressure control mechanisms was hypothesized almost a century ago (Bradbury and Eggleston, ) and is now supported by a body of basic and clinical research (Fig.…”
mentioning
confidence: 99%
“…Future research on the relationship between vestibular system integrity and symptoms of postural hypotension in older age is needed to verify this hypothesis. Nevertheless, recent work has demonstrated that activation of the vestibular system, especially the otolith organs, directly affects cerebral blood flow independently of blood pressure and end tidal carbon dioxide . Deficient otolith organs could therefore contribute to cerebral hypoperfusion, and it is well documented that cerebral hypoperfusion leads to symptoms of light‐headedness.…”
Section: Discussionmentioning
confidence: 99%